Analysis of retained deuterium on Be-based films: Ion implantation vs. in-situ loading. (December 2018) - Mateus, R.; Porosnicu, C.; Lungu, C.P.; Cruz, C.; Siketić, Z.; Radović, I. Bogdanović; Hakola, A.; Alves, E.; ,
Highlights: Thin Be-based coatings were produced by HiPIMS with and without incorporation of deuterium. The HiPIMS coatings produced without deuterium were implanted by 2 × 10 17  ion/cm 2, 15 keV 2 H + ions. All the coatings were analysed by IBA techniques (EBS, RBS, NRA, ToF-ERDA). Despite distinct deuterium profiles, similar retained amounts are revealed in the films loaded by ion implantation or by HiPIMS, assuring ion implantation as a competitive and reliable method for fuel incorporation in Be, Be+O and Be+O+C thin films. Abstract: Pure Be, Be-O and Be-O-C thin coatings were deposited using high-power impulse magnetron sputtering (HiPIMS) with and without incorporation of deuterium. The coatings produced without deuterium were implanted afterwards with 15 keV 2 H + ion beams with a fluence limited to 2 × 10 17 ion/cm 2 in order to mitigate the damage imposed by ion irradiation and prevent a fast gas release. The as-deposited and as-implanted coatings were analysed by IBA techniques, namely by elastic and Rutherford backscattering spectrometries (EBS and RBS, respectively), nuclear reaction analysis (NRA) and by time-of-flight elastic recoil detection analysis (ToF-ERDA). Despite distinct deuterium depth profiles in the implanted samples, the results show that for the present ion implantation and deposition parameters, similar retained amounts are revealed in the films loaded by ion implantation or during the HiPIMS deposition, assuring ion implantation as a competitive and reliable method for fuel incorporation in thin Be-based films for retention studies in controlled conditions.